Curcumin inhibits hepatic stellate cell activation via suppression of succinate-associated HIF-1α induction. (15th November 2018) - She, Linlin; Xu, Dan; Wang, Zixia; Zhang, Yirui; Wei, Qingli; Aa, Jiye; Wang, Guangji; Liu, Baolin; Xie, Yuan
Abstract: Purpose: Aberrant succinate accumulation emerges as a unifying mechanism for inflammation and oxidative stress. This study aims to investigate whether curcumin ameliorates hepatic fibrosis via blocking succinate signaling. Methods: We investigated the effects of curcumin on hepatic succinate accumulation and liver fibrosis in mice fed a high-fat diet (HFD). Meanwhile, we stimulated mouse primary hepatic stellate cells (HSCs) with succinate and observed the inhibitory effects of curcumin on succinate signaling. Results: Oral administration of curcumin and metformin combated mitochondrial fatty acid oxidation and reduced hepatic succinate accumulation due to the inhibition of succinate dehydrogenase (SDH) activity and demonstrated inhibitory effect on hepatic fibrosis. In mouse primary HSCs, curcumin prevented succinate- and CoCl2 -induced hypoxia-inducible transcription factor-1α (HIF-1α) induction via suppression of ROS production and effectively reduced gene expressions of Col1α, Col3α, fibronectin and TGF-β1 with inflammation inhibition. Knockdown of HIF-1α with small interfering RNA blocked the action of succinate to induce HSCs activation, indicative of the essential role of HIF-1α in succinate signaling. Conclusions: Hepatic succinate accumulation served as a metabolic signal to promote liver fibrosis through HIF-1α induction. Curcumin reduced succinate accumulation by combating fatty acid oxidation and prevented HSCs activation by blocking succinate/HIF-1α signaling pathway. Highlights: Succinate accumulated in hepatocytes due to enhanced fatty acid oxidation. Succinate stabilized and activated HIF-1α by impairing PHDs. Succinate induced inflammation and HSC activation dependent on HIF-1α. Curcumin alleviated liver fibrosis by blocking succinate/HIF-1α signaling pathway.